Finiteness of the space of n-cycles for a reduced (n − 2)-concave complex space - Barlet, Daniel (Épijournal de géométrie algébrique, 2017)
EPIGA, Volume 1 (2017), Nr. 5 We show that for n ≥ 2 the space of closed n-cycles in a strongly (n − 2)-concave complex space has a natural structure of reduced complex space locally of finite dimension and represents the functor " analytic family of n-cycles " parametrized by Banach analytic sets. Nous montrons que, pour n ≥ 2, l'espace des n-cycles fermés dans un espace complexe fortement (n − 2)-concave a une structure naturelle d'espace complexe réduit localement de dimension finie et que cet espace représente le foncteur " famille analytique de n-cycles " paramétrée par des ensembles analytiques banachiques.